The Desire for Social Robots to Support English Language Learners: Exploring Robot Perceptions of Teachers, Parents, and Students - Louie, Belinda; Björling, Elin A.; Kuo, Annie Camey (Frontiers in Education, 2021)
Currently there are 4.9 million English Language Learners (ELLs) in the United States, however, only 2% of educators are trained to support these vulnerable students. Educational robots show promise for language acquisition and may provide valuable support for ELLs, yet, little is known about social robots for this population. Inviting participants as cultural informants can ensure that the robot is appropriately designed, situated and adopted into that educational community. Therefore, we conducted an exploratory study using interactive group interviews with 95 ELLs (kindergarten through fifth grade) from 18 different home language backgrounds. We also interviewed 39 ELL parents and eight elementary school educators to understand their views of educational robots. Responses to robot images suggested a preference for a popular educational robot. Parents expressed a strong desire for educational robots to support their children at school. While children embraced the idea of a robot at school, some expressed concerns about the potential for robots to be disruptive. School educators saw the potential for educational robots to support teachers in meeting instructional needs but also raised salient concerns. Exploring social robots with ELLs as cultural informants was a valuable exploration to determine important factors in social robot design and implementation for a diverse educational setting.